JILBAB, HIJAB DAN AURAT PEREMPUAN (Antara Tafsir Klasik, Tafsir Kontemporer dan Pandangan Muslim Feminis) - Fathonah K. Daud (Al Hikmah: Jurnal Studi Keislaman, 2013)
Jilbab, either as fashion or term, new known in Indonesia in the 1980s. Before that the Indonesian people already know the "kerudung" (as the head cover loosely), which is used in a limited circle. Problems arise in line with the swift on the jilbab wearers in this country, which of course wearing the jilbab has been no longer simply becoming a demand of syariah, but more than that. Jilbab just as a fashion, privacy, sometimes as a resistance and strength, as imaging or even to attract public sympathy. Here the jilbab loaded with meaning and importance. On the other side, the veil is also seen as patriarchal culture biased, or vice versa seen as a liberation. At this point, jilbab has entered the arena of contestation-a play of meaning and interpretation. Power relations played and the mutual attraction between the normative theologians and Muslim feminists. For that reason this paper attempts to outline some of the differences between the views of classical scholars, contemporary scholars till explain how Muslim feminists have done a reinterpretation and deconstruction toward the classical commentators about the veil, including the hijab and ‘awrat’ of women.